Library and reading culture: solving problems in our own hands (Eurasian Journal of Learning and Academic Teaching, 2024)
The decline of library use and the decline of reading culture have become important concerns in modern society. This research paper examines the problems associated with these problems and suggests that the solution lies in the hands of individuals within society. By emphasizing the importance of libraries and reading culture, encouraging lifelong learning, encouraging community engagement, and leveraging technology, we can lead a renaissance in libraries and foster a renewed love of reading.